A diverse gastropod fauna from the shallow marine carbonate platform of the Yangou section (south China) in the immediate aftermath of the Permian–Triassic mass extinction. (20th January 2021) - Sun, Xin; Qiu, Xincheng; Tihelka, Erik; Yang, Hao; Sun, Dongying; Tong, Jinnan; Tian, Li
Abstract : The Permian–Triassic mass extinction (PTME), the most devastating extinction event in Phanerozoic history, has witnessed the demise of almost 80% of marine gastropod genera. Despite the vast scale of the extinction event, the recovery of some groups of marine gastropods has been curiously fast, contrasting with the delayed recovery of many other marine clades. Understanding the rapid recovery of gastropods after the PTME represents a major palaeobiological conundrum, since oxygen‐dependent taxa are expected to have been severely impacted by anoxic oceanic conditions of the PTME. The controversial microbialite refuge hypothesis has been proposed as a potential explanation of this pattern, arguing that marine invertebrates were associated with oxygen‐producing microbial mats during the PTME, which provided a suitable microhabitat for survival within hostile anoxic conditions. To better understand the dynamics of gastropod recovery after the PTME, we studied a gastropod fauna collected from the basal Daye Formation (earliest Triassic) at the Yangou section in Leping County, Jiangxi Province, south China, allowing us to capture a snapshot of the marine fauna immediately after the PTME. Altogether, 13 microgastropod species belonging to 12 genera were recorded, representing the most diverse Induan (earliest Triassic) gastropod fauna in the world known to date. The fact that the Yangou assemblage, along with the second most diverse Griesbachian gastropod fauna from the Wadi Wasit section in Oman, is not associated with microbial buildups implies that microbial mats probably did not play a key role as refuges for marine invertebrates during the PTME. On the other hand, the Yangou fauna suggests that non‐anoxic shallow lagoon systems were more likely to have acted as refuges for marine invertebrates during the PTME. Abstract : A diverse gastropod fauna from the basal Daye Formation at the Yangou Permian–Triassic boundary section of South China is presented, with the known highest taxonomic diversity of gastropod in the immediate aftermath of Permian–Triassic mass extinction (PTME). There is no microbial buildups found in the study Yangou section and the gastropods were enriched in the dark muddy limestone, implying that the non‐anoxic shallow lagoon systems, rather than microbial mats, were more likely to be the refuges of marine invertebrates during PTME.